2021
DOI: 10.3390/healthcare9030294
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality Attitudes and Beliefs Survey (SABS): Validation of the Instrument for the Spanish Nursing Students

Abstract: Patient sexuality is a fundamental subject in nursing student’s education. However, beliefs about patient sexuality can influence the care offered. The aim of this psychometric study was to describe the validation process and the psychometrics properties of the Sexuality Attitudes and Beliefs Survey (SABS) for Spanish nursing students. The convenience sample was 283 nursing students from a state university in Spain. Participants ranged from 18 to 30 years (M = 19.66; SD = 1.85). Data collection happened in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Therefore, all nurses should graduate with the skills to provide sexual care. However, the individual personalities, beliefs, and attitudes of nurses may constitute a barrier in providing this care (Aguiar Frias et al, 2021; Öz et al, 2021; Sharon et al, 2020). Although various studies have evaluated the beliefs, attitudes, and self‐efficacy of nursing students regarding sexual health care, more studies are needed in this area (Cesnik & Zerbini, 2017; Öz et al, 2021; Sung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, all nurses should graduate with the skills to provide sexual care. However, the individual personalities, beliefs, and attitudes of nurses may constitute a barrier in providing this care (Aguiar Frias et al, 2021; Öz et al, 2021; Sharon et al, 2020). Although various studies have evaluated the beliefs, attitudes, and self‐efficacy of nursing students regarding sexual health care, more studies are needed in this area (Cesnik & Zerbini, 2017; Öz et al, 2021; Sung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The positive attitudes and beliefs of nursing students regarding sexual care enable them to address sexuality as a part of the patients' holistic nursing care (Aguiar Frias et al, 2021; Öz et al, 2021). When the SABS total scores were examined in the present study, it was specified that male nursing students had more negative attitudes and beliefs regarding sexual care than female nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the instrument will be a questionnaire composed by socio-demographic data and different scales. On the one hand, the Sexuality Attitudes and Beliefs Survey (SABS) [ 51 ] and in its Spanish version [ 52 ], Portuguese [ 53 ] or Italian [ 54 ] versions, will be used as instrument, previously validated by the partner universities. This SABS will reinforce the possible results obtained in this protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The scale is unidimensional, and the original form has a Cronbach’s alpha coefficient of 0.750, and a test-retest of 0.820 [ 51 ]. The Portuguese version has been validated by removing one item (N3) that improves internal consistency for social sciences, reaching a Cronbach’s alpha coefficient of 0.720, and in the test-retest of 0.800 [ 53 ], while the Spanish study reported a Cronbach’s alpha coefficient of 0.651 and is finally maintaining the 12 items [ 52 ]. The validated instrument in the Italian version shows adequate internal consistency (alpha = 0.76) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%